2012
DOI: 10.3109/0886022x.2012.747967
|View full text |Cite
|
Sign up to set email alerts
|

Form CMS-2728 Data Versus Erythropoietin Claims Data: Implications for Quality of Care Studies

Abstract: Medical Evidence Report Form CMS-2728 data is frequently used to study US dialysis patients, but the validity of these data have been called into question. We compared predialysis erythropoietin use as recorded on Form CMS-2728 with claims data as part of an assessment of quality of care among hemodialysis patients. Medicare claims were linked to Form CMS-2728 data for 18,870 patients. Dialysis patients, 67 years old or older, who started dialysis from 1 June 2005 to 31 May 2007 were eligible. Logistic and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For example, one study found that there was underreporting of nursing home utilization on form 2728 . Two other studies revealed discrepancy on erythropoietin use between forms 2728 and claims data . Furthermore, inaccuracies of reported pre‐dialysis nephrology care, vascular access, and cause of ESRD for glomerular diseases were documented .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study found that there was underreporting of nursing home utilization on form 2728 . Two other studies revealed discrepancy on erythropoietin use between forms 2728 and claims data . Furthermore, inaccuracies of reported pre‐dialysis nephrology care, vascular access, and cause of ESRD for glomerular diseases were documented .…”
Section: Discussionmentioning
confidence: 99%
“…The law requires that the comorbidity section of the form needs to be completed by the nephrologist whereas other sections can be completed by support staff in the dialysis facility. Significant time, effort and extensive access to the medical record may be needed for physicians to accurately complete the 2728 form, and previous studies have confirmed that the current system of manual completion is often erroneous . Data from the previous 10 years can be used for completion, but evaluating such voluminous data from multiple Electronic Medical Records (EMR) systems is time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Our sensitivity analyses of presumably ESA-naïve patients used information provided on the Medical Evidence Report, which has been shown to substantially misclassify pre-ESRD use of ESAs in two validation studies. 30 , 31 Finally, we were unable to study other ESAs, including epoetin beta, epoetin delta, epoetin omega, biosimilar epoetins, or the long-acting methoxy polyethylene glycol–epoetin beta, all of which are available in other countries, but not currently used in the United States due to patent restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, another issue is that data reported to the CMS may be inaccurate. Furthermore, the USRDS data derived from the Medical Evidence report submitted to the CMS are often inaccurate (30)(31)(32)(33)(34). The effects of increased use of financial incentives to improve the accuracy of dialysis facilities' self-reported data are also unclear.…”
Section: Data Issues With Kidney Disease Surveillance Systemsmentioning
confidence: 99%